61.0k views
0 votes
Solve: 62x - 3 = 6-2x+1

x = -1

x = 0

x = 1

x = 4     




User Frigon
by
5.8k points

2 Answers

1 vote

Final answer:

To solve the equation 62x - 3 = 6 - 2x + 1x, combine like terms, add and subtract terms to isolate x, and simplify the solution.

Step-by-step explanation:

To solve the given equation, 62x - 3 = 6 - 2x + 1x:

  1. Combine like terms: 63x - 3 = 6 - x
  2. Add x to both sides: 63x + x - 3 = 6
  3. Combine like terms: 64x - 3 = 6
  4. Add 3 to both sides: 64x - 3 + 3 = 6 + 3
  5. Combine like terms: 64x = 9
  6. Divide both sides by 64: 64x / 64 = 9 / 64
  7. Simplify: x = 9 / 64

Therefore, the solution to the equation is x = 9 / 64.

User Ken Block
by
5.6k points
4 votes

Answer: X=1 Is the answer on edge 2023 :)

Step-by-step explanation: X=1

User Pankaj Cheema
by
5.7k points